The Assessment of culture learning : issues, frameworks, and techniques. - Adler, Emily (My University, 2008)
A survey of current practices for teaching and evaluating culture learning in foreign language classrooms. Advocates using the three Ps of culture (products, practices, and perspectives) for beginning language learners.
Color poster with text and graphs describing research conducted by Emily Adler under the supervisor of Anne Cummings-Hlas.
Keywords: Intercultural communication.; Multicultural education.; Language and languages--Study and teaching.; Language and culture.